Management of Historic Assets in the Perspective of Good Corporate Governance - Anisa Tus Saidah; Puji Handayati; Satia Nur Maharani (CV. AFDIFAL MAJU BERKAH, 2023)
The purpose of this study is to find out whether Historical Asset Management is following the theory of Good Corporate Governance. The researcher chose the research location for historic assets at the Regional XI Cultural Preservation Center, which is located in Trowulan District, Mojokerto Regency. The researcher chose the Cultural Preservation Center for Region XI as the research location because it is an institution that manages historical assets and the Mojokerto district is the number one place that has historical heritage and the largest and widest Majapahit kingdom in Indonesia. This study used a qualitative method with a phenomenological approach and conducted interviews with two informants, namely Mr. S and Mr. H. In terms of the implementation of the management reviewed from the perspective of Good Corporate Governance theory, the principles of this theory have been applied to the performance of BPK XI. In addition, the valuation, disclosure, and reporting of historic assets in BPK XI have been reported as fixed assets in the balance sheet and disclosed in the notes to the financial statements.